Dangers in the Use of Staplers in Liver Surgery - Riga, Angela (The Royal College of Surgeons of England, 2007)
The use of endoscopic vascular staplers has become common practice in recent years both in open and minimally invasive surgery. The technological advances, however, are not free of problems. In our practice, we have come across two cases where the Endopath ETS Flex 45 Endoscopic Articulating Linear Cutter failed with dangerous consequences.